Histamine: neural circuits and new medications. Issue 1 (18th September 2018) - Scammell, Thomas E; Jackson, Alexander C; Franks, Nicholas P; Wisden, William; Dauvilliers, Yves
Abstract: Histamine was first identified in the brain about 50 years ago, but only in the last few years have researchers gained an understanding of how it regulates sleep/wake behavior. We provide a translational overview of the histamine system, from basic research to new clinical trials demonstrating the usefulness of drugs that enhance histamine signaling. The tuberomammillary nucleus is the sole neuronal source of histamine in the brain, and like many of the arousal systems, histamine neurons diffusely innervate the cortex, thalamus, and other wake-promoting brain regions. Histamine has generally excitatory effects on target neurons, but paradoxically, histamine neurons may also release the inhibitory neurotransmitter GABA. New research demonstrates that activity in histamine neurons is essential for normal wakefulness, especially at specific circadian phases, and reducing activity in these neurons can produce sedation. The number of histamine neurons is increased in narcolepsy, but whether this affects brain levels of histamine is controversial. Of clinical importance, new compounds are becoming available that enhance histamine signaling, and clinical trials show that these medications reduce sleepiness and cataplexy in narcolepsy.